1960
DOI: 10.1071/bi9600456
|View full text |Cite
|
Sign up to set email alerts
|

The Symbiotic Synthesis of Auxin by Legumes and Nodule Bacteria and its Eole in Nodule Development

Abstract: When subterranean clover (Trifolium subterraneum L.) plants were grown for 3 weeks over distilled water, tryptophan could be detected in the root medium of both sterile cultures and those inoculated with Rhizobium trifolii 3 days earlier. Auxin could be detected only in the inoculated medium. The auxin had the chromatographic and growth properties of indole·3-acetic acid (IAA). Since nodule bacteria produce auxin only in the presence of tryptophan, which is a probable precursor of lAA, it is suggested that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 13 publications
(17 reference statements)
2
26
0
Order By: Relevance
“…That is most likely to be the regulation of the hormone level, in particular that of auxin, by acting at the level of its synthesis and/or transport. These indirectly affect nodule formation (Kefford et al, 1960;Hunter, 1987;1989;Hirsch et al, 1989;Fukuhara et al, 1994;Wu et al, 1996) and the partitioning of photosynthates (Brenner and Cheikh, 1995). This is further supported by the synergistic response observed to HBR and auxin (Mandava, 1988).…”
Section: Resultssupporting
confidence: 56%
“…That is most likely to be the regulation of the hormone level, in particular that of auxin, by acting at the level of its synthesis and/or transport. These indirectly affect nodule formation (Kefford et al, 1960;Hunter, 1987;1989;Hirsch et al, 1989;Fukuhara et al, 1994;Wu et al, 1996) and the partitioning of photosynthates (Brenner and Cheikh, 1995). This is further supported by the synergistic response observed to HBR and auxin (Mandava, 1988).…”
Section: Resultssupporting
confidence: 56%
“…The It should be noted that the nutrient medium we used for most experiments was less complex than normal plant tissue culture media (18,29). Root nodule tissue is able to fix atmospheric N2 and is probably autonomous for the production of both auxin (9) and cytokinin (22). Nevertheless it is possible that the low growth rate of detached nodules may have been caused by a deficiency in some nutrient or growth factor such as the ethyl alcohol-soluble factor reported to interact with cytokinin to stimulate cell proliferation in pea root cortex explants (13).…”
Section: Resultsmentioning
confidence: 99%
“…Nutman (13) has stated that, with few exceptions, only curled root hairs become infected. It has been suggested that IAA is involved in nodulation, but the mechanism of such an effect is not clear (9,13,16,20,21,22 Although there is evidence for a local effect of combined nitrogen on nodulation, few attempts have been made to propose a mechanism. Virtanen (26) has suggested that nitrate inhibition occurs through the formation of nitrite which reacts to form a nitriteleghemoglobin complex.…”
mentioning
confidence: 99%